Pengaruh Tingkat Pendidikan dan Jam Kerja terhadap Pendapatan Pekerja Perempuan (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
This Research Aimed To Tested The Influence Of Education Level And Work Hours Toward The Earning Of Women Workers. The Sample In This Research Is The Women Who Work And Living In The District Of Sidodadi, Samarinda City. The Research Data Was Collected Through Questionnaires That Are Processed And Analyzed Using Multiple Regression Analysis. The Method Of Collecting Samples Used In This Research Is Nonprobability Sampling With Purposive Sampling Technique. To Test The Hypothesis In This Research, This Research Used Assumptions Klsik Test, R Test, R2 Adjusted F Test And T Test. The Result Of This Research Data Shows That Work Hours Variable And Education Level Have Positive And Significant Influence Toward The Earnings Of Women Workers In The District Of SidodadiKeywords: The Earnings Of Women Workers